Proboscis lateralis: a case report of nasal aplasia with complete agenesis of maxilary and ethmoidal sinuses - Abdul Rasheed, Shamim Rahman; Al- Hadeethi, Yahia F. Hussein; Wan Leman, Wan Ishlah (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
We report a child with Proboscis Lateralis with nasal aplasia and complete agenesis of maxillary and ethmoidal sinuses. This is a rare congenital malformation. Embryological basis has not been proven, and it is often associated with facial malformation. However, no such abnormality was noted in our patient. This condition is diagnosed clinically and confirmed radiologically of which CT scan plays a pivotal role. Reconstructive surgery is planned at the age of fifteen years.